Property Inheritance Rights and Female Political Participation in India - Bharti Nandwani; Punarjit Roychowdhury (Global Labor Organization (GLO), 2024)
This paper examines whether granting property inheritance rights to women improves their participation in politics as election candidates in India. In patriarchal societies like India, conservative gender norms often discourage women from active political engagement, reinforced by social sanctions for non-compliance. Additionally, political involvement demands significant time and financial resources, making it particularly challenging for women. Enhancing property rights has the potential to financially empower women, alleviating both social and economic constraints. Using state-level variation in legal changes to women's property rights and leveraging large-scale administrative data on elections in India, we find that improved property rights lead to a rise in female candidacy and an increased likelihood of electoral success for women. We also observe that regional parties field more female candidates, and there is a notable increase in the entry of 'new' female candidates post-reform. Furthermore, using extensive household survey data, we show that this rise in political participation is driven by improvements in women's financial autonomy, education, and economic awareness following the inheritance reforms. Our analysis confirms that these results are not confounded by pre-existing trends and are robust to treatment effect heterogeneity.
Keywords: J16; D72; K11; O12; 330; Gender; India; Female Political Participation; Property Rights